FACTORS THAT INFLUENCE THE LEVEL OF FOOD SECURITY OF RICE PARMERS HOUSEHOLDS IN PATOKBEUSI DISTRICT SUBANG REGENCY WEST JAVA - Lies Sulistyowati; Slamet Yuliyadi (AGRIBEST, 2019)
Food is a basic human need that adequacy is a top priority. Stability in a country will be good when food for people assured. Therefore, food security becomes important things. Food security at the household level is the  important thing because food security begins with the smallest level. In this case, the household food security of farmers is also interesting to note because they are a food producer. Patokbeusi District, Subang Regency is one of the potential rice producers, but the dynamics of land tenure affect the food security of farm households. This study aims to determine the major rice production which influence the level of household food security of farmers and socio-economic factors that influence it. The research method used is a survey technique using primary and secondary data. The sampling method uses stratified  random sampling with 97 respondents consisting of rice farmers. The analysis technique uses logistic regression and descriptive techniques. The results from this study as follow: characteristics of farmers are farmers with medium land, with a level of high school education, aged over 40 years, and production average  6.6 tonnes ha/year. Rice farmers in Patokbeusi classified as food secure with indicators of accessibility, continuity, stability, and quality of food. While, the socio-economi factors that influence the rate of household food security is the level of education of farmers and the amount of expenditure to food.